2018
DOI: 10.1080/21688370.2018.1487249
|View full text |Cite
|
Sign up to set email alerts
|

AMPK in regulation of apical junctions and barrier function of intestinal epithelium

Abstract: Gut epithelium covers the inner layer of the gastrointestinal tract and provides a physical barrier to separate the host from its external environment, and its barrier function is critical for maintaining host health. AMP-activated protein kinase (AMPK) as a master regulator of energy metabolism plays a critical role in epithelial barrier function. AMPK activation promotes epithelial differentiation and facilitates cell polarity establishment, both of which strengthen epithelial barrier. In addition, AMPK prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 121 publications
2
49
1
1
Order By: Relevance
“…; Zhu et al . ). In addition, a negative correlation of placental AMPK phosphorylation in relation to body mass index and birth weight was reported (Jansson et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Zhu et al . ). In addition, a negative correlation of placental AMPK phosphorylation in relation to body mass index and birth weight was reported (Jansson et al .…”
Section: Resultsmentioning
confidence: 97%
“…Finally, we were not able to describe the detailed mechanisms of action of glutamine on colonic barrier function. Recently, AMPK activation has been reported to enhance enterocytes polarization and ameliorate the assembly of tight junction proteins, leading to an improvement of intestinal barrier function [66], probably through the AMPK–CDX2 pathway [67]. The role of AMPK in the regulation of gut barrier function in ABA mice and its modulation by glutamine requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK), a highly conserved serine/threonine kinase, is widely known as a regulator of energy homeostasis to promote ATP generation and energy restoration [21]. When the overall energy level in a cell deceases because of increased demands by various stimulates, AMPK is activated through phosphorylation by upstream kinases or directly triggered by an elevated AMP/ ATP ratio [38]. Under heat stress, AMPK phosphorylation is downregulated in HeLa and HEK293 cells [39].…”
Section: Itemsmentioning
confidence: 99%
“…Accumulating studies have shown that activation of AMPK by pharmacological or nutraceutical approaches strengthens the epithelial barrier function [21,24,38]. AICAR treatment enhances the barrier function in Caco-2 cells [42].…”
Section: Itemsmentioning
confidence: 99%